New LA-ICP-MS cryocell and calibration technique for sub-millimeter analysis of ice cores. Issue 226 (2015) - Sneed, Sharon B.; Mayewski, Paul A.; Sayre, W.G.; Handley, Michael J.; Kurbatov, Andrei V.; Taylor, Kendrick C.; Bohleber, Pascal; Wagenbach, Dietmar; Erhardt, Tobias; Spaulding, Nicole E.
Abstract: Ice cores provide a robust reconstruction of past climate. However, development of timescales by annual-layer counting, essential to detailed climate reconstruction and interpretation, on ice cores collected at low-accumulation sites or in regions of compressed ice, is problematic due to closely spaced layers. Ice-core analysis by laser ablation–inductively coupled plasma–mass spectrometry (LA-ICP-MS) provides sub-millimeter-scale sampling resolution (on the order of 100 μm in this study) and the low detection limits (ng L −1 ) necessary to measure the chemical constituents preserved in ice cores. We present a newly developed cryocell that can hold a 1 m long section of ice core, and an alternative strategy for calibration. Using ice-core samples from central Greenland, we demonstrate the repeatability of multiple ablation passes, highlight the improved sampling resolution, verify the calibration technique and identify annual layers in the chemical profile in a deep section of an ice core where annual layers have not previously been identified using chemistry. In addition, using sections of cores from the Swiss/Italian Alps we illustrate the relationship between Ca, Na and Fe and particle concentration and conductivity, and validate the LA-ICP-MS Ca profile through a direct comparison with continuous flow analysis results.